1994
DOI: 10.1128/jb.176.17.5550-5553.1994
|View full text |Cite
|
Sign up to set email alerts
|

tRNA genes of Streptomyces lividans: new sequences and comparison of structure and organization with those of other bacteria

Abstract: Three closely linked Streptomyces lividans tRNA genes encoding two tRNA(Lys)s and a tRNA(Gly) were cloned and sequences. The structure of tRNA(Gly) is unusual for eubacterial tRNAs. Including those in previous reports (R. Sedlmeier and H. Schmieger, Nucleic Acids Res. 18:4027, 1990, and R. Sedlmeier, G. Linti, K. Gregor, and H. Schmieger, Gene 132:125-130, 1993), 18 S. lividans tRNA genes were physically mapped on the chromosome of the closely related strain Streptomyces coelicolor A3(2). The structure and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…We also found that for the majority of cloned 3′ halves, there was evidence supporting the existence of a terminal CCA sequence, with either the entire CCA sequence being present or some portion of it (Supplementary Table 1). The terminal CCA sequence is added post-transcriptionally to the majority of tRNAs in S. coelicolor ( 25 ), in contrast to the situation in E. coli , where the terminal CCA is encoded within all tRNA genes ( 26 ). This suggested that the tRNA cleavage products were derived from mature tRNAs that were capable of being aminoacylated, and not from immature/precursor tRNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that for the majority of cloned 3′ halves, there was evidence supporting the existence of a terminal CCA sequence, with either the entire CCA sequence being present or some portion of it (Supplementary Table 1). The terminal CCA sequence is added post-transcriptionally to the majority of tRNAs in S. coelicolor ( 25 ), in contrast to the situation in E. coli , where the terminal CCA is encoded within all tRNA genes ( 26 ). This suggested that the tRNA cleavage products were derived from mature tRNAs that were capable of being aminoacylated, and not from immature/precursor tRNA molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the association between tRNA genes and rRNA genes in Streptomyces revealed a striking paradigm, with no tRNAs so far found to be associated with any rRNA operons. Sedlmeier and collaborators (204) proposed that the lack of tRNA genes with rRNA genes might be characteristic for all actinomycetes. Based on the first reports that initiator tRNAs from Streptomyces griseus and S. rimosus lack CCA ends (74, 128) and on later publications indicating that potential tRNA Pro , tRNA Thr , and tRNA Tyr genes associated with site-specific recombination in Streptomyces also lack CCA termini (132,143,197), Plohl and Gamulin (185) predicted that most, if not all, tRNA genes in S. rimosus do not encode a CCA terminus.…”
Section: Trna Rrna and Gene Expression In S Rimosusmentioning
confidence: 99%
“…It is common for bacterial tRNAs to be encoded by multicistronic operons. A multicistronic tRNA transcript may contain more than one tRNA, or rRNA and mRNA in addition to tRNA (Wawrousek and Hansen 1983;Komine et al 1990;Sedlmeier et al 1994). Some bacteria have genetically encoded 3Ј terminal CCA for all tRNAs, whereas others only encode CCA for fractions of their total tRNAs (Deutscher 1984;Minagawa et al 2004).…”
Section: Introductionmentioning
confidence: 99%